Diffusion-weighted imaging of the dentate nucleus after repeated application of gadolinium-based contrast agents in multiple sclerosis - Eisele, Philipp; Szabo, Kristina; Ebert, Anne; Radbruch, Alexander; Platten, Michael; Schönberg, Stefan; Gass, Achim (Magnetic resonance imaging, 2019)
Objective - Over the last years several studies reported an increased signal intensity (SI) of the dentate nucleus (DN) on unenhanced T1-weighted images after repeated application of gadolinium-based contrast agents (GBCAs), suggesting gadolinium deposition. The aim of this study was to investigate with diffusion-weighted MRI possible tissue abnormalities of the DN in multiple sclerosis (MS) patients. - Material and methods - We retrospectively identified seventeen patients with at least six contrast-enhanced MRI examinations by using the linear GBCA gadopentate dimeglumine and twenty-three patients with the exclusive use of the macrocyclic contrast agent gadoterate meglumine followed by another 3 Tesla MRI scan including unenhanced T1-weighted and diffusion-weighted images. - Results - In the linear GBCA group, we found significant differences of the DN-to-pons SI ratio on unenhanced T1-weighted images (1.13±0.05) when compared to the macrocyclic GBCA group (0.97±0.03; p<0.001). However, we found no significant differences between apparent diffusion coefficient (ADC) values of the DN in both groups (linear GBCA group: 0.82±0.04×10−3mm/s2; marcocyclic GBCA group: 0.79±0.04×10−3mm/s2; p=0.15). - Conclusions - Our results do not suggest that there is any difference in ADC values in the T1-hyperintense DN, which does not indicate a difference in tissue integrity between patients exposed to macrocyclic or linear GBCAs.